LIVER AND KIDNEY HISTOPATOLOGY OF LANDRACE SWINE GIVEN WATER HYACINT FROM LEAD CONTAMINATED WATER - Dewi, Ni Kadek Nining Laksmi; Winaya, Ida Bagus Oka; Dharmawan, Nyoman Sadra (Buletin Veteriner Udayana, 2017)
The aim of this study is to determine the effect of water hyacinth ( Eichornia crassipes ) collected from Lead (Pb) polluted water in feed to histopathological changes in pig’s liver and kidney. A total of eight Landrace pigs were used in this study, consisted of four groups: pigs were fed without hyacinth (A), pigs were fed with 2.5% hyacinth (B), pigs were fed with 5.0% hyacinth (C), and pigs were fed with 7.5% hyacinth (D). The sample of dead pigs were dissected at the end of study to examined the liver and kidney. Both organs sample were  immersed in a fixative solution of 10% neutral buffered formalin. The samples were then processed for tissue processing by using Hematoxillin-Eosin method before performing histophatological examination by using 100x, 200x and 400x magnificence under a microscope. Data were then analyzed descriptively by comparing the pathological changes in the liver and kidneys between groups. The results showed that the administration of water hyacinth ( Eichornia crassipes ) collected from Lead (Pb) polluted water causes a histopathological changes in the liver and kidneys of Landrace pigs. The changes include degeneration, necrosis and inflammation.
Keywords: Babi Landrace, eceng gondok, timbal (Pb), histopatologi, hati dan ginjal